2017
DOI: 10.1515/afmnai-2017-0005
|View full text |Cite
|
Sign up to set email alerts
|

Translation, Cultural Adjustment and Evaluation of Reliability and Validity of “Quality of Life Enjoyment and Satisfaction Questionnaire – Short Form” for Patients with Schizophrenia

Abstract: The Quality of Life Enjoyment and Satisfaction Questionnaire -Short Form is the most often used scale for measuring the quality of life of patients with psychiatric diseases. The aim of this research was to analyze the possibilities for measuring the quality of life in clinical conditions on the sample of patients with schizophrenia by using this scale. The study was conducted on the group including 153 patients with schizophrenia at the Institution for Accommodation of Adults "Male Pčelice", Kragujevac. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The total score is out of 27, which indicates the severity of depressive symptoms. It is subdivided into five categories: minimal or none (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), moderately severe (15)(16)(17)(18)(19), and severe (20)(21)(22)(23)(24)(25)(26)(27). The last part was Q-LES-Q-SF which captures the enjoyment and satisfaction over the past week.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The total score is out of 27, which indicates the severity of depressive symptoms. It is subdivided into five categories: minimal or none (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), moderately severe (15)(16)(17)(18)(19), and severe (20)(21)(22)(23)(24)(25)(26)(27). The last part was Q-LES-Q-SF which captures the enjoyment and satisfaction over the past week.…”
Section: Data Collectionmentioning
confidence: 99%
“…They are among the commonly used measures in psychiatric research (18). Their validity and reliability have been established in several settings and populations (19)(20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…A key feature of this questionnaire is that it emphasizes the subjective perceptions of individuals physical, psychological, and social domains of daily life [10]. Furthermore, this questionnaire has been translated in several languages and validated in diverse groups of individuals with different socio-economic backgrounds and lifestyles, as well as with other health conditions besides the psychiatric ones [2,[8][9][10][11][12][13][14][15][16][17]. The results of the previous studies revealed that the Q-LES-Q-SF questionnaire exhibited sound psychometric properties and it has been used as a QOL questionnaire in more than 100 peer-reviewed publications [17].…”
Section: Introductionmentioning
confidence: 99%